Combining creative writing and narrative analysis to deliver new insights into the impact of pulmonary hypertension. Issue 1 (5th June 2017) - Goddard, Julia C; Armstrong, Iain J; Kiely, David G; Elliot, Charlie A; Charalampopoulos, Athanasios; Condliffe, Robin; Stone, Brendan J; Sabroe, Ian
Abstract : Introduction: Pulmonary hypertension is life limiting. Delays in diagnosis are common, and even after treatment has been initiated, pulmonary hypertension has marked effects on many aspects of social and physical function. We believed that a new approach to examining disease impact could be achieved through a combination of narrative research and creative writing. Methods: Detailed unstructured narrative interviews with people with pulmonary hypertension were analysed thematically. Individual moments were also summarised and studied using creative writing, in which the interviewer created microstories from narrative and interview data. Stories were shared with their subjects, and with other patients, clinicians, researchers and the wider public. The study was carried out in hospital and in patients' homes. Results: Narrative analysis generated a rich data set which highlighted profound effects of pulmonary hypertension on identity, and demonstrated how the disease results in very marked personal change with ongoing and unpredictable requirement for adaptation. The novel methodology of microstory development proved to be an effective tool to summarise, communicate and explore the consequences of pulmonary hypertension and the clinical challenges of caring for patients with this illness. Conclusions: A holistic approach to treatment of chronic respiratory diseases such as pulmonary hypertension requires and benefits from explicit exploration of the full impacts of the illness. Narrative analysis and the novel approach of targeted microstory development can form a valuable component of the repertoire of approaches to effectively comprehend chronic disease and can also facilitate patient-focused discussion and interventions.